PENENTUAN TINGKAT EFISIENSI ALOKATIF DAN EFISIENSI TEKNIS PADA USAHATANI JAGUNG MANIS ( Zea mays saccharata L. ) DI KECAMATAN KUPANG TIMUR - Oktavia Oni; Wiendiyati Wiendiyati; Johanna Suek (Buletin Ilmiah Impas, 2020)
Research about the determining of allocative and technical efficiency level of sweet corn farming in East Kupang Sub District aims to find out the effect of the use of production factors toward sweet corn production; to analyze the level of allocative efficiency of its use; and to analyze the level of production technical efficiency of sweet corn. The research location was chosen by purposive sampling with the consideration that Oesao village and Pukdale are villages where produce sweet corn in East Kupang Sub District. The sample of research respondents was taken by simple random sampling with 79 respondents consisting of 35 farmers from Oesao village and 44 farmers from Pukdale village. The collect of data had been carried out as long as February to March 2020. The reseach results showed that the factors of land, seed, and urea production significantly affected the production of sweet corn, while the factors of NPK, pesticides and labor production had no significant effect. The level of efficiency can be reached through allocate production inputs precisely. In this case, by reducing the use of land and urea fertilizer, on the other hand, by adding the use of seeds. Also, the farmer production level technically is not efficient yet with the average of actual production level is 10,408 grains or around 1,487 kg, while the average frontier production level is 28,146.64 grains or around 4,021 kg. There are 39 farmers who their technical efficiency in low level category, than, 28 farmers in moderate level category, and as many as 12 farmers have reached a level of technical efficiency.